Adaptogens Stimulate Neuropeptide Y and Hsp72 Expression and Release in Neuroglia Cells - Panossian, Alexander G.; Wikman, Georg; Kaur, Punit; Asea, Alexzander (Frontiers in Neuroscience, 2012)
The beneficial stress-protective effect of adaptogens is related to the regulation of homeostasis via mechanisms of action associated with the HPA axis and the regulation of key mediators of the stress response, such as molecular chaperones, stress-activated c-Jun N-terminal protein kinase (JNK1), Forkhead box O (FoxO) transcription factor, cortisol and nitric oxide (NO). However, it still remains unclear what the primary upstream targets are in response to stimulation by adaptogens. The present study addresses this gap in our knowledge and suggests that an important target for adaptogen mediated stress-protective effector functions is the stress hormone neuropeptide Y (NPY). We demonstrated that ADAPT-232, a fixed combination of adaptogens Eleutherococcus senticosus root extract, Schisandra chinensis berry extract, Rhodiola rosea root extract SHR-5, and its active constituent salidroside, stimulated the expression of NPY and Hsp72 in isolated human neurolgia cells. The central role of NPY was validated in experiments in which pre-treatment of human neuroglia cells with NPY-siRNA and HSF1-siRNA resulted in the significant suppression of ADAPT-232-induced NPY and Hsp72 release. Taken together our studies suggest that the stimulation and release of the stress hormones, NPY and Hsp72, into systemic circulation is an innate defense response against mild stressors (ADAPT-232), which increase tolerance and adaptation to stress.